2000
DOI: 10.1046/j.1360-0443.2000.9545295.x
|View full text |Cite
|
Sign up to set email alerts
|

Natural disasters and alcohol consumption in a cultural context: the Great Hanshin Earthquake in Japan

Abstract: More attention should be placed on drinking in the cultural context where a disaster occurs. It may sometimes deter, rather than encourage, drinking among the affected population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 0 publications
0
20
0
4
Order By: Relevance
“…Other sources, however, have noted decreased alcohol consumption after disasters. Alcohol consumption reportedly decreased after the Great Hanshin Earthquake in Japan (Shimizu et al, 2000), and sales of alcohol in the United States fell significantly after the September 11 attacks (US Census Bureau Service Sector Statistics Division, 2001;Whitaker, 2001aWhitaker, , 2001b. If alcohol abuse/dependence does not develop anew after disasters, their presence in the population provides opportunities to recognize cases and provide treatment.…”
Section: Discussionmentioning
confidence: 98%
“…Other sources, however, have noted decreased alcohol consumption after disasters. Alcohol consumption reportedly decreased after the Great Hanshin Earthquake in Japan (Shimizu et al, 2000), and sales of alcohol in the United States fell significantly after the September 11 attacks (US Census Bureau Service Sector Statistics Division, 2001;Whitaker, 2001aWhitaker, , 2001b. If alcohol abuse/dependence does not develop anew after disasters, their presence in the population provides opportunities to recognize cases and provide treatment.…”
Section: Discussionmentioning
confidence: 98%
“…52 Evidence does suggest that dramatic reductions in outlet availability of alcohol outlets can have significant impacts on drinking behavior and negative alcoholrelated consequences. 15,53 Another approach could be to reduce the availability of more problematic beverages such as malt liquors and fortified wines. Preliminary studies indicate some success using this approach, 54 although larger studies with more rigorous designs are required to establish the effectiveness of such an approach.…”
Section: Discussionmentioning
confidence: 99%
“…There have been conflicting findings regarding post-event outcomes (on the individual and community level) and antecedent risk factors. [6][7][8][9][10][11][12] The disaster literature has been growing quickly in the past decade, spanning studies evaluating physical as well as psychiatric/psychological outcomes following natural disasters and manmade disasters (e.g., terrorist activity) alike. For instance, in reviewing dozens of studies, Rodriguez et al found that although many persons are resilient in the face of exposure to disasters (with up to half of persons never developing symptoms), there is a vulnerable minority that may develop mood, anxiety, and posttraumatic stress disorder (PTSD) symptoms that persist for 18 months or more 13 depending on level of exposure and antecedent risk factors.…”
Section: Introductionmentioning
confidence: 99%